Airway epithelial cell-specific deletion of HMGB1 exaggerates inflammatory responses in mice with muco-obstructive airway disease - Mao, Yun; Patial, Sonika; Saini, Yogesh (Frontiers in Immunology, 2023)
High mobility group box 1 (HMGB1), a ubiquitous chromatin-binding protein required for gene transcription regulation, is released into the extracellular microenvironment by various structural and immune cells, where it is known to act as an alarmin. Here, we investigated the role of airway epithelium-specific HMGB1 in the pathogenesis of muco-obstructive lung disease in Scnn1b-transgenic (Tg+) mouse, a model of human cystic fibrosis (CF)-like lung disease. We hypothesized that airway epithelium-derived HMGB1 modulates muco-inflammatory lung responses in the Tg+ mice. The airway epithelium-specific HMGB1-deficient mice were generated and the effects of HMGB1 deletion on immune cell recruitment, airway epithelial cell composition, mucous cell metaplasia, and bacterial clearance were determined. The airway epithelium-specific deletion of HMGB1 in wild-type (WT) mice did not result in any morphological alterations in the airway epithelium. The deficiency of HMGB1 in airway epithelial cells in the Tg+ mice, however, resulted in significantly increased infiltration of macrophages, neutrophils, and eosinophils which was associated with significantly higher levels of inflammatory mediators, including G-CSF, KC, MIP-2, MCP-1, MIP-1α, MIP-1β, IP-10, and TNF-α in the airspaces. Furthermore, as compared to the HMGB1-sufficient Tg+ mice, the airway epithelial cell-specific HMGB1-deficient Tg+ mice exhibited poor resolution of spontaneous bacterial infection. The HMGB1 deficiency in the airway epithelial cells of Tg+ mice did not alter airway epithelial cell-specific responses including epithelial cell proliferation, mucous cell metaplasia, and mucus obstruction. Collectively, our findings provide novel insights into the role of airway epithelial cell-derived HMGB1 in the pathogenesis of CF-like lung disease in Tg+ mice.